ANALISIS YURIDIS PELAKSANAAN PERJANJIAN PEMBORONGAN PEKERJAAN PENIMBUNAN TANAH UNTUK KEPENTINGAN PEMBANGUNAN JALAN TOL DI KECAMATAN MEDAN HELVETIA KOTA MEDAN - KIKI HANDOKO SEMBIRING (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. T. Keizerina Devi A3. Suprayitno Land reclaiming for toll road implemented by the government today is intended to build infrastructure in the entire Indonesian territory. . The work is carried out by contractors, PT. Hutama Karya Infrastruktur and PT. Alghazali Satria Perkasa who have legal entity and are bound in a tendering contract of land reclaiming for Medan-Binjai Section I toll-road. The research used legal normative method. The nature of the research is descriptive analytic method which describes, explains, and analyzes the research problems by finding their solutions. The result of the research shows that regulation on the tendering contract is in accordance with Chapter VII A of Book III, Article 1601b until Article 1616 of the Civil Code, Law No. 18/1999 on Construction Service and Perpres No. 16/2018 as the fifth amendment of Perpres No. 4/2015 on the fourth amendment of Perpres No. 54/2010 on Procuring the Government’s Goods and Services. The obstacles found in the field are natural factors and condition in the field. The solution is by coping with the problems in the field and by performing negotiation about the late paying by PT. Hutama Karya Infrastruktur and PT. Alghazali Satria Perkasa.Keywords: Tendering Contract, Land Reclaiming, Toll Road